Monopoly with resale - Giacomo Calzolari; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2004)
This paper illustrates the intricacies associated with the design of revenue-maximizing mechanisms for a monopolist who expects her buyers to resell in a secondary market. We consider two modes of resale: the first is to a third party who does not participate in the primary market; the second is inter-bidders resale, where the winner in the primary market resells to the losers. The main contribution is in showing how revenue-maximizing mechanisms can be designed investigating the optimal informational linkage with the secondary market. To control the price in the resale game, the monopolist must design an allocation rule and a disclosure policy that optimally fashion the beliefs of the participants in the resale market. We show that it is generically impossible to maximize revenue through deterministic selling procedures and disclosing only the decision to trade with a particular buyer. To create the optimal informational linkage, the monopolist may need to induce stochastic allocations and disclose also the price paid in the primary market. The optimal allocation rule and disclosure policy maximize the expected sum of the bidders' resale-augmented virtual valuations under the constraints imposed by the sequential rationality of the bidders' offers in the resale game.
Keywords: D44; D82; 330; optimal information linkage between primary and secondary markets; disclosure policy; stochastic allocations; resale-augmented virtual valuations; Monopol; Auktionstheorie; Dynamisches Spiel; Unvollkommene Information; Theorie